Marx's attempt to leave philosophy - Brudney, Daniel (Harvard University Press, 1998)
Daniel Brudney traces the development of post-Hegelian thought from Ludwig Feuerbach and Bruno Bauer to Karl Marx's work of 1844 and his Theses on Feuerbach, and concludes with an examination of The German Ideology. Brudney focuses on the transmutations of a set of ideas about human nature, the good life, and our relation to the world and to others; about how we end up with false beliefs about these matters; about whether one can, in a capitalist society, know the truth about these matters; and about the critique of capitalism which would flow from such knowledge. Brudney shows how Marx, following Feuerbach, attempted to reveal humanity's nature and what would count as the good life, while eschewing and indeed polemicizing against "philosophy"--Against any concern with metaphysics and epistemology. Marx attempted to avoid philosophy as early as 1844, and the central aims of his texts are the same right through The German Ideology. There is thus no break between an early and a late Marx; moreover, there is no "materialist" Marx, no Marx who subscribes to a metaphysical view, even in The German Ideology, the text canonically taken as the origin of Marxist materialism. Rather, in all the texts of this period Marx tries to mount a compelling critique of the present while altogether avoiding the dilemmas central to philosophy in the modern era. Table of Contents: Abbreviations Introduction Themes from the Young Hegelians Feuerbach's and Marx's Complaint against Philosophy The Interest of These Texts Chapter by Chapter 1. Feuerbach's Critique of Christianity The Critique of Christianity The Method of The Essence of Christianity Comparisons The Geistiger Naturforscher 2. Feuerbach's Critique of Philosophy The Status of Philosophy The Method of the Critique of Philosophy The Content of the Critique of Philosophy Problems Antecedents Final Comment 3. Bruno Bauer Self-Consciousness State and Civil Society The Critique of Religion Bauer's Method Assessment 4. The 1844 Marx I: Self-Realization Species Being: Products Species Being: Enjoyments The Human Relation to Objects Species Being: Immortality The Human Self-Realization Activity 5. The 1844 Marx II: The Structure of Community Completing One Another Mediation with the Species 3 Digression on Community 6. The 1844 Marx III: The Problem of Justification The Workers' Ignorance of Their True Nature The Problem of Justification The Problem of Communists' Ends and Beliefs Marx's 1844 Critique of Philosophy The Problem of the Present 7. The Theses on Feuerbach Fundamental Relations/Orientations Thesis Eleven Labor The Practical-Idealist Reading The Problem of the First Step Thesis Six 8. The German Ideology I: More Anti-Philosophy Some General Comments The Attack on the Young Hegelian Empirical Verification Anti-Philosophy I Anti-Philosophy II Transformation 9. The German Ideology II: The Picture of the Good Life and the Change from 1844 Division of Labor Community Self-Activity The Change from 1844 10. The German Ideology III: The Critique of Morality (and the Return to Philosophy) What Is the Problem with Morality? The (Weak) Sociological Thesis The Strong Sociological Thesis and the Structural Thesis Morality and Moral Philosophy under Communism Can The German Ideology Justify a Condemnation of Capitalism? Returning to Philosophy Conclusion Notes Index Reviews of this book: "[Marx's Attempt to Leave Philosophy] is plainly the work of a thoughtful and intelligent philosopher. The discussions of Bruno Bauer and Marx's writings of 1844-6, in particular, are valuable resources for students of German philosophy of the 1840s."--Brian Leiter, Times Literary Supplement "Brudney's work offers some fascinating insights into the world of the Young Hegelians from whence Marx came. It also makes some subtle points about the epistemology of moral theory and about the communitarian aspects of Marx's vision that are important for contemporary philosophy." --R. Hudelson, Choice